Συγκριτική αξιολόγηση υδατικών διαλυμάτων γλυκερόλης και αιθανόλης, ως πράσινοι διαλύτες για την εκχύλιση πολυφαινολικών ουσιών από φλοιούς πατάτας (Solanum tuberosum), υποβοηθούμενης με υπερήχους - Παλαιολόγου, Ειρήνη; Βασιλείου, Αρετή (2021)
Potato peels, an abundant food industry waste, were used as a source to recover polyphenolic antioxidants, using aqueous mixtures of two bio-solvents, ethanol and glycerol and ultrasonication. The optimization of the extraction and the evaluation of the extraction efficiency were put on a comparative basis and carried out first by performing a Box-Behnken experimental design and then by implementing kinetics. The optimization showed that out of the three variables considered, only solvent composition displayed a significant difference, whereas the liquid-to-solid ratio and temperature were virtually the same, irrespective of the solvent system used. It was found that under optimized conditions, the extraction yield in total polyphenols was 8.71 and 9.11 mg caffeic acid equivalents per gram dry weight, for water/glycerol and water/ethanol mixtures, respectively. The kinetic assay revealed that extraction with the solvent composed of water/ethanol was faster compared with water/glycerol, giving corresponding effective diffusion coefficients of 0.46×10−11 and 0.33×10−11 m2 s−1. However, both solvent systems were equally efficient in extracting polyphenols. Furthermore, some discrepancies were seen regarding the antioxidant activity of the extracts. The extracts obtained with both water/ethanol and water/glycerol, under optimised conditions, were analysed by liquid chromatography-mass spectrometry, and they were demonstrated to possess almost identical polyphenolic profile, the predominant compound being chlorogenic acid. This finding suggested that there is no selectivity issue. The outcome of the study illustrated that bio-solvents such as ethanol and glycerol could be employed in green processes, destined to produce extracts enriched in polyphenolic antioxidants, from waste resources.